(untitled) (ENTHYMEMA, 2013)
The translation into Italian of the essay by Ol’ga Vladimirovna Slivickaja «Vdrug» u Tolstogo: neozidannoe v mire zakonomernogo, published on the journal Russkaja Literatura in 2012. The essay is dedicated to the unexpected and unforeseeable behaviour by some Tolstoyan characters who seem alien to the logical and controlled universe created by his novels. The scholar shows how even in this fictional world there is room for unexpected and unpredictable actions, which find their origin in the depth of the character’s consciousness.